An Analysis of Idiosyncrasy in Ernest Hemingway's Characterization in The Selected Short Stories - Dewi Fitriani (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2018)
This study analyzed the characterization and idiosyncrasy in Ernest Hemingway’s selected short stories. The researcher chooses Ernest Hemingway’s selected short stories because of its famous literary works that makes the researcher interested to know the story is about. The purpose of this study are to find out the types of characterization and the idiosyncrasy used in Ernest Hemingway’s selected short stories. This study used content analysis approach by Elo and Kyngas (2007), Kirscbaum’s theory of characterization and theory of stylistic and idiosyncrasy by Leech and Short (2007). Besides, the researcher also used other theories such as, Abid, Denzin & Lincoln, Miles & Huberman, Mack, et al, Reams to support the concepts. The data were collected by identifying 10 Ernest Hemingway’s selected short stories that contain types of characterization and then found the idiosyncrasy in Ernest Hemingways selected short stories. The findings of this study shows Ernest Hemingway used indirect characterization to present the characters in the stories. There are 27 quotations of 10 selected short stories that shows it. The researcher also had found the idiosyncrasy through stylistic concept of Ernest Hemingway. There are structural and lexical points. The researcher found ‘it was’ to stress the object pronoun and ‘there’ to stress the subject that included in structural point. The researcher also found ‘and’ to start the sentences, an animal to represent the main problem, and verbal irony as his figure of speech. In this study, the suggestions are directed to the students in the English Department, who are interested in the literary study, particularly of the characterization and the idiosyncrasy in the short stories. This research can be a source to support the study of literature such as characterization, the idiosyncrasy, Ernest Hemingway, and to conduct research in the same field.